Comparison of Indonesia and Korea Video Tourism Advertisements Found in YouTube Using Social Semiotic - Nadia Andriani; Hamzah Hamzah (English Language and Literature, 2021)
This study aims to compare the differences and the similarities between two video tourism advertisements of Indonesia and South Korea through three levels of metafunction. The three levels of metafunctions are: 1) the level of ideational metafunction, 2) the level of interpersonal metafunction, and 3) the level of textual metafunction. The Systemic Functional Linguistics theory by Halliday, Visual Grammar theory by Kress and Van Leeuwen and generic structure analysis theory by Cheong were applied to analyze this research. The method used in this research was a descriptive research method. The data in this research were texts and images used in two video tourism advertisements. The results of the study show that they share one similarity and fourteen differences in the level of ideational metafunction. Then, there are six similarities and eight differences in the interpersonal level. Meanwhile, there are four differences and no similarities found for textual metafunction. The conclusion obtained from the findings is that they are more different rather than similar and the differences in how they produces the video tourism ads are affected by the differences in cultural background of the videos which are represented through speech and visual and lead to the different ways of producing structure of clauses and selection of words in the three levels of metafunction.